Etnografi Diri: "Mengada dengan dan untuk yang Liyan" - Johanes Supriyono (Antropologi Indonesia, 2011)
This paper is an autoethnographic exploration which would like to show that culture is always in the process of constructing those that are present in various track events. Through the exposure of various stages of life and moments of encounters with Others, the author wants to confirm his argument on how culture is an arena of discourses that is continually constructed, in which also involves power relations between Self and Others. Using Abu Lughod’s approach and several contributions from philosophical thinking, the author would like to state that the theoretical journey and life trajectory is a continuity which shows the fundamental argument, that culture is an arena of contestation that is based on power relations between the self and the Other. Keywords: construction, culture, Self, Other, discourse, contestation